Efficacy of dispersion of magnesium silicate (talc) in papermaking - Vipul Singh Chauhan; Nishi Kant Bhardwaj (Arabian Journal of Chemistry, 2017)
The understanding of the dispersion chemistry of papermaking grade fillers is as important as their effect on paper. Magnesium silicate (talc) is one of the major fillers used for papermaking. It is hydrophobic and chemically inert. The dispersion chemistry of talc of different particle sizes was studied with wetting agent (non-ionic triblock copolymer) and anionic dispersant (sodium salt of polyacrylic acid). Both wetting agent and dispersant were added in talc slurry separately and in combination. The dispersion behavior was studied through measuring the Brookfield viscosity. The wetted and dispersed talc was also added to paper to understand its effect on papermaking process and paper properties. Wetting and dispersion changed the colloidal charge chemistry of talc making it more anionic which reduced the talc retention in paper. Lowering the particle size of talc significantly improved the light scattering coefficient (LSC) of paper and decreased its retention. Controlling colloidal charge of papermaking suspension with cationic polyacrylamide polymer helped in protecting the retention of talc without affecting the LSC of both filler and paper.